Revised status of Omolicna subgenus Agoo (Hemiptera: Auchenorrhyncha: Fulgoroidea: Derbidae) with a new species from Costa Rica and new country records - Bahder, Brian W.; Bartlett, Charles R.; Helmick, Ericka E.; Barrantes, Edwin A. Barrantes; Echavarria, Marco A. Zumbado; Goss, Erica M.; Ascunce, Marina S. (Zootaxa, 2020)
An ongoing survey for novel phytoplasmas and viruses that affect palms (Arecaceae) and their potential vectors is being conducted in Costa Rica. During that survey, a new species of derbid planthopper (Hemiptera: Fulgoroidea) from the palm Astrocaryum alatum H.F. Loomis was found in Heredia State and is here described as Agoo dahliana sp. n. Omolicna dubia Caldwell and O. latens Fennah were also found on coconut palms (Cocos nucifera L.) and represent new country records. Sequence data for the cytochrome c oxidase subunit I (COI) were generated for 9 ingroup (Omolicna Fennah) and 1 outgroup (Neocenchrea Metcalf) taxa; and for 18S ribosomal RNA gene were generated for 8 ingroup plus 2 outgroup taxa (Neocenchrea, Cenchrea Westwood). These data were compiled with available data from GenBank and BOLD for maximum likelihood phylogenetic reconstruction for Omolicna. These results, plus morphological evidence, support changing the status of the genus-group name Agoo Bahder & Bartlett from subgenus within Omolicna to full genus, resulting in the new combination of Agoo xavieri Bahder & Bartlett. Based on the original description and illustration of the genitalia of Omolicna rubrimarginata Fennah (from Trinidad), we transfer this species to Agoo, creating the combination Agoo rubrimarginata (Fennah), and bringing the total number of species in this genus to three, with A. dahliana sp. n. and A. xavieri currently only known from Costa Rica. Based on both molecular and morphological evidence, O dubia is transferred to Anchimothon Fennah. A key to differentiate the species of Agoo is presented.